Investigation of crystalline phases in the [alpha]-Fe2O3/[alpha]-Al2O3 system - Ristić, Mira (Array, 2009)
Summary: Mixtures containing the desired weight ratios of α-Fe2O3 and γ-AlOOH were homogenized in the planetary mill, then pressed into tablets and heated up to 1200 °C. All samples were characterized by X-ray diffraction, Mössbauer spectroscopy, Field emission scanning electron microscopy and Energy dispersive X-ray analysis. Two types of solid solutions of general formula α-(AlxFe1-x)2O3 were found; one solid solution was closely related to α-Fe2O3 the other to α-Al2O3 The terminal solid solubility limits, r = 27.0 ± 0.5 mole ratio of α-Al2O3 in α-Fe2O3 and r = 9.0 ± 0.5 of α-Fe2O3 in α-Al2O3 were determined. The Mössbauer spectra showed a broadening of spectral lines and a decrease in the hyperfine magnetic field of α-Fe2O3 with incorporation of Al3+ ions in the α-Fe2O3 structure. For mole fractions between x = 0.4 and 0.70, the Mössbauer spectra were considered as the superposition of a sextet and quadrupole doublet(s). In this concentration range the samples showed an almost constant value of hyperfine magnetic field. For x = 0.90 and 0.93, the Mössbauer spectra were considered as a superposition of two quadrupole doublets, whereas for x = 0.95 the superposition of two quadrupole doublets and one singlet was considered. The origin of this singlet with the isomer shift close to zero is not clearly understood. FE-SEM showed a strong sintering effect on the particles in all samples in the α-(AlxFe1-x)2O3 system